2019
DOI: 10.1038/s41598-019-46077-z
|View full text |Cite|
|
Sign up to set email alerts
|

Association of TLR4 and TLR9 polymorphisms and haplotypes with cervical cancer susceptibility

Abstract: single nucleotide polymorphisms (sNps) in TLR genes may serve as a crucial marker for early susceptibility of various cancers including cervical cancer. the present study was therefore designed to ascertain the role of TLR4 and TLR9 sNps and haplotypes to hrHpV infection and cervical cancer susceptibility. The study included 110 cervical cancer biopsies and 141 cervical smears from age-matched healthy controls of Gujarati ethnicity of Western India. hrHPV 16 and 18 were detected using Realtime pCR. eight sNps,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 58 publications
1
24
1
3
Order By: Relevance
“…The correlation between anogenital tumour or pretumour lesions and HPV infection has been well described [18]. There is general consensus in stating that patients treated for high grade CIN or cervical cancer are at increased risk of invasive neoplasia and our study confirms this trend [5][6][7][8][9][10][11][12][13][14]16].…”
Section: Anogenital Regionsupporting
confidence: 83%
See 1 more Smart Citation
“…The correlation between anogenital tumour or pretumour lesions and HPV infection has been well described [18]. There is general consensus in stating that patients treated for high grade CIN or cervical cancer are at increased risk of invasive neoplasia and our study confirms this trend [5][6][7][8][9][10][11][12][13][14]16].…”
Section: Anogenital Regionsupporting
confidence: 83%
“…Host immunoresponse influence the effectiveness of viral clearance: primary immunodeficiency disorders but also polymorphisms in genes such as TLRs (Toll-Like receptors) and NF-kB networks are associated with higher risk of lesions [18]. Also secondary immunodeficiencies either infection-related (HIV) or iatrogenic (chemotherapy or biological drugs) elevate the risk of HPV related malignancies [4].…”
Section: Introductionmentioning
confidence: 99%
“…A previous meta-analysis conducted by Yang et al (78) identified an association between TLR gene polymorphisms and the risk of cervical cancer. The results revealed that white populations carrying the C allele of the TLR 9 1486 T/C gene polymorphism and the A allele of the TLR 9 G2848A gene polymorphism were significantly associated with an increased risk of developing cervical cancer (78,79). TLR 9 has been previously reported to promote cervical intraepithelial neoplasia (CIN) progression in women from Tunisia (80).…”
Section: Factors That Contribute To the Development Of Cervical Cancermentioning
confidence: 99%
“…A number of genetic changes like single nucleotide polymorphisms (SNPs) within the TLR genes has been reported in humans which can influence receptor binding and function, that ultimately influences the risk for the inflammatory diseases as well as cancers [21]. Although there have been numerous studies reporting the impact of polymorphisms on TLR function and disease development, there is still a lot of contradiction in terms of outcomes [22].…”
Section: Tlrs Genetics and Regulation Of Signalingmentioning
confidence: 99%
“…All TLRs except TLR3, which exclusively uses the TIR-domain-containing adapter-inducing interferon-β (TRIF) pathway, use MYD88 as the downstream adapter protein that activate the classical/canonical inflammatory signaling pathway [26][27][28][29]. After activation with their specific ligands, TLRs recruit MYD88, leading to subsequent activation of three main transcription factors: interferonregulatory factors (IRF3, IRF5 and IRF7), NF-kB, MAPK and AP1 [21][22][23][24][25][27][28][29][30][31][32]. Subsequently, it promote the transcription of cytokines such as TNF-α, IL-6 and IL-1, chemokines and interferons which are key mediators of inflammation [30].…”
Section: Tlrs Genetics and Regulation Of Signalingmentioning
confidence: 99%